Daphne decline: what is the causal agent(s)? - Fránová, J; Lesemann, D-E (Acta virologica, 2007)
A double infection of Daphne mosaic virus (DapMV) and an associated bacilliform virus was observed in the samples of diseased Daphne mezereum shrubs that showed mosaic patterns, precocious leaves reddening, defoliation, repeated flowering with subsequent declining. Extensive aggregations of bacilliform particles (166-370 x 65 nm and 169-233 x 68-78 nm) occurred in the nucleus or perinuclear space of root and leaf tissues suggesting that the virus might belong to the genus Nucleorhabdovirus, family Rhabdoviridae. However, the single bacilliform virions appeared occasionally in the cytoplasm of the leaf cells. We supposed that occurrence of the mixed virus infection could be the cause of D. mezereum decline in the Czech Republic.
Keywords: Microscopy, Electron, Transmission; Česká republika; Daphne; buněčné jádro; nemoci rostlin; Cell Nucleus; transmisní elektronová mikroskopie; Plant Roots; Plant Viruses; kořeny rostlin; Czech Republic; Plant Leaves; listy rostlin; rostlinné viry; Plant Diseases